The incorporation of graphene oxide into polysulfone mixed matrix membrane for CO2/CH4 separation - Zahri, K. (Institute of Physics Publishing, 2016)
Carbon dioxide (CO2) is often found as the main impurity in natural gas, where methane (CH4) is the major component. The presence of CO2 in natural gas leads to several problems such as reducing the energy content of natural gas and cause pipeline corrosion. Thus it must be removed to meet specifications (CO2 ≤ 2 mol%) before the gas can be delivered to the pipeline. In this work, hollow fiber mixed matrix membrane (MMM) were fabricated by embedding graphene oxide (GO) into a polysulfone (PSf) polymer matrix to improve membrane properties as well as its separation performance towards CO2/CH4 gas. The membrane properties were investigated for pristine membrane and mixed matrix membrane filled with filler loading of 0.25%. The synthesized GO and properties of fabricated membranes were characterized and studied using TEM, AFM, XRD, FTIR and SEM respectively. The permeance of pure gases and ideal selectivity of CO2/CH4 gas were determined using pure gas permeation experiment. GO has affinity towards CO2 gas. The nanosheet structure creates path for small molecule gas and restricted large molecule gas to pass through the membrane. The incorporation of GO in PSf polymer enhanced the permeance of CO 2 and CO2/CH4 separation from 64.47 to 86.80 GPU and from 19 to 25 respectively.